Der Pluralismus des Rechts im Zeitalter der Globasierung. Zum Rechtsbegriff in der Rechtssoziologie - Rehbinder, M. (Інститут держави і права ім. В.М. Корецького НАН України, 2005)
Социология права избрала путь исследования особенностей живого права. Особое внимание обращается на внутренний плюрализм права, когда недопустимым есть плюрализм понятий права в внутреннем праве суверенного государства. Только государственная сфера – это точка соприкосновения и существования живого права. О плюрализме понятий права может говорить только как о политическом идеале,
но не как о критерии права. Транснациональный плюрализм права характерен тем, что суверенитет не может раскрываться путем передачи суверенных прав, потому что в противном случае национальное государство потеряет
свое качество носителя правопорядка. The sociology of law chose the way of studying the features of the living law. Special attention is paid to
the inner pluralism of law where the pluralism of law as a part of the internal state law is deemed unacceptable. Only the state sphere is considered as a crossing point and living place of the living law. One can talk about the pluralism of law only in terms of political ideal but not as of a criterion of law. The transnational pluralism of law is characterized by that the sovereignty may not be exercised by the transfer of sovereign rights because in the opposite case a national state will lose its quality of the carrier of the legal order.